The effect of green purchase intention on emerging market consumers’ clothing purchase behaviour in South Africa - Makhitha, KM (International Journal of Management and Sustainability, 2024)
The purpose of this study was to determine the influence of the green purchase intention of emerging market consumers on their green purchase behaviour in South Africa. The calls by the United Nations’ (UN) Sustainable Development Goals (SDGs) for consumers and organizations to act and behave sustainably have generated much interest in green consumer behaviour. In SA, calls have also been made for clothing companies to create awareness about the impact of clothing buyer behaviour on the environment. Organizations should also enhance consumer knowledge of their green buying behaviour and the effect this has on the environment. A survey was conducted online among the emerging consumers in Soweto, Johannesburg, targeting 300 respondents. The results confirmed that environmental knowledge and social/peer influence have an impact on green purchase intention and that green purchase intention does influence consumer behaviour. The effect of green purchase intention on green clothing behaviour was found to be higher than the effect of environmental knowledge and social/peer pressure on purchase intention. Clothing firms and policymakers should focus on raising awareness, disseminating information, and using peer pressure to enhance customers’ inclination to make environmentally friendly purchases. This, in turn, will impact the buying behaviour of consumers in emerging markets.